Mechanochemically Assisted Synthesis of a Ru Catalyst for Hydrogen Evolution with Performance Superior to Pt in Both Acidic and Alkaline Media - Li, Feng; Han, Gao‐Feng; Noh, Hyuk‐Jun; Ahmad, Ishfaq; Jeon, In‐Yup; Baek, Jong‐Beom (Advanced materials (Weinheim), 2018)
Catalysts are at the heart of the hydrogen evolution reaction (HER) for the production of pure and clean hydrogen. For practical applications, the scalable synthesis of efficient HER catalysts, which work in both acidic and alkaline media, is highly desired. In this work, the mechanochemically assisted synthesis of a Ru catalyst with HER performance surpassing Pt in both acidic and alkaline media is reported. Mass production of this Ru catalyst can be achieved via a two‐step procedure: the mechanochemical reaction between graphite and dry ice produces edge‐carboxylic‐acid‐functionalized graphene nanoplatelets (CGnP); mixing a Ru precursor and the CGnP in an aqueous medium introduces Ru ions, which coordinate on the CGnP. Subsequent annealing results in uniform Ru nanoparticles (≈2 nm) anchored on the GnP matrix (Ru@GnP). The efficient Ru@GnP catalyst can be easily powered by a single silicon solar cell using a wireless integration device. The self‐powered device exhibits robust hydrogen evolution under the irradiation of standard AM 1.5 solar light. This work provides a new opportunity for the low‐cost mass production of efficient and stable catalysts for practical applications. The mechanochemically assisted synthesis of a ruthenium (Ru) on graphene nanoplatelet (GnP) catalyst is explored to demonstrate efficient and stable hydrogen evolution performance surpassing Pt in both acidic and alkaline media. The synthesis procedures start from uniform anchoring Ru ions on mechanochemically driven edge‐carboxylic‐acid‐functionalized graphene nanoplatelets (CGnP) to produce Ru@CGnP, which becomes Ru@GnP after reduction and annealing.